Biological Age as a New Risk Factor for Diabetic Retinopathy in Patients with Type 2 Diabetes Mellitus - N. M. Agarkov; O. L. Fabrikantov; I. V. Lev (Oftalʹmologiâ)
For the prevention of diabetic retinopathy, it is important to study risk factors, among which, along with the duration of type 2 diabetes mellitus, the level of glycemia, obesity, chronological age is indicated, but biological age is not considered as a potential risk factor, although biological age more objectively than chronological characterizes pathological changes at the cellular level and processes apoptosis. Purpose: to study biological age as a new risk factor for diabetic retinopathy in patients with type 2 diabetes mellitus. 580 patients aged 45–59 years with diabetic retinopathy and type 2 diabetes mellitus, whose biological age was calculated according to the Voitenko V.P. et al. methodology, took part in the study on the basis of the S.N. Fedorov National medical research center “MNTK Eye Microsurgery”. The correspondence of biological and chronological age was established in 124 patients, the excess (acceleration) of the chronological biological age in 357 patients and the excess of the biological chronological age in 99 patients. In the subsequent analysis, the first two groups were considered. Among 45–59yearold patients with type 2 diabetes mellitus, the incidence of diabetic retinopathy was 19.82 ± 1,32 cases per 100 examined, which is statistically significantly higher (p < 0.001) compared to patients of the same age with type 2 diabetes mellitus with a chronological biological age — 10.24 ± 1.51 cases per 100 examined. Significant differences in the compared groups were also revealed in the values of the chronological age of diagnosis of diabetic retinopathy in this endocrine disease — 47.69 ± 1.24 years in patients with accelerated biological age and 50.23 ± 0.92 years in patients with matching biological and chronological age (p < 0.01). The biological age of diagnosis of diabetic retinopathy, respectively, was 56.13 ± 0.83 years and 49.61 ± 1.11 years (p < 0.001). The difference in the development of diabetic retinopathy in patients 45–59 years old with type 2 diabetes mellitus by biological age was 6,52 ± 1,24 years among patients with accelerated biological age and 0.62 ± 0.09 years among patients with matching biological and chronological age (p < 0.001). Consequently, the acceleration of biological age is a significant and new risk factor for diabetic retinopathy in patients aged 45–59 years with type 2 diabetes mellitus.